Identification of a nonsense mutation at the 5' end of the TSC2 gene in a family with a presumptive diagnosis of tuberous sclerosis complex. Issue 1 (January 1996) - Vrtel, R; Verhoef, S; Bouman, K; Maheshwar, M M; Nellist, M; van Essen, A J; Bakker, P L; Hermans, C J; Bink-Boelkens, M T; van Elburg, R M; Hoff, M; Lindhout, D; et al.
Abstract : Tuberous sclerosis complex (TSC) is an autosomal dominantly inherited disease with a high mutation rate. It is clinically a very variable disorder and hamartomas can occur in many different organs. TSC shows genetic heterogeneity; one gene, TSC1, is on chromosome 9q34, and the second gene, TSC2, on chromosome 16p13.3. Clinical criteria for diagnosis have been established, but diagnosis of patients with minimal expression of the disease can be very difficult. In children the phenotype is often incomplete or not fully assessable. Hence mildly affected subjects, at risk for severely affected offspring, may remain undiagnosed. The detection of (small) mutations in the tuberous sclerosis gene located on chromosome 16 (TSC2) has recently become possible and may be helpful in the diagnosis of ambiguous cases. To our knowledge, this is the first report of a point mutation in the TSC2 gene in a familial case of tuberous sclerosis. A nonsense mutation was detected in a family in which the father had only minor signs hinting at tuberous sclerosis. The son had multiple cardiac tumours and white patches, but full clinical investigation was impossible in this child. This case illustrates that mutation analysis can contribute to a diagnosis of tuberous sclerosis in families with an incomplete phenotype.